Pivot: Sebuah Tinjauan Weberian atas Rasionalitas Tindakan - Albertus Bambang Suprijanto; Tony Rudyansjah (Antropologi Indonesia, 2021)
Second conversion along with the increasing of welfare and age is a common phenomenon that occurs among the urban middle class. In this case, the achievement of the ultimate goal of life must be prepared through daily habits. Religion is then considered as a vehicle that can bring them through life to realize what they aspire to in the future. Religious morality is used as a guide in living daily life. In fact, not all changes in life views can be categorized as second conversions. In this paper, Max Weber's conception of the “calling” is used as an analytical tool to discuss the changes in the way of life experienced by the urban middle class. Based on the concept of calling, this paper divides changes in life views into three categories based on the rationality of their actions, namely the FOMO, YOLO, and PIVOT groups. The results of the analysis showed that only the PIVOT group actually experienced a second conversion. They deal with all life situations by pivoting using religious morality as its axis. This study uses an ethnographic method, in which the informants come from the urban middle group in Greater Jakarta.